PENGARUH KONSENTRASI DAN INTERVAL WAKTU PEMBERIAN PUPUK ORGANIK CAIR (POC) DAN KUDA LAUT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG (Vigna sinensis L.) - Jasmi Jasmi; Said Mahdjali; Juni Gunawan (Universitas Teuku Umar, 2018)
This research was carried out in the village of Seuneubok subdistrict of West Aceh Regency Hero Johan, starting from 2 may until 7 September 2012. The purpose of the study is to know the influence of concentration and time interval of granting POC sea horse star appropriate towards growth and production plants of Eggplant. The seeds are used in this research are the seeds of Eggplant varieties Bungo F1, cow manure, Urea fertilizer, SP-36 and KCl as a basic fertilizer, and POC sea horse stars. This study used a Randomized Design Group (RAK) factorial pattern 3 x 4 with 3 Deuteronomy, there are two factors that are examined, namely the concentration factor consists of 4 levels, namely 0 1 cc/liter cc/liter water, water, water cc/liter, 3 5 cc/liter and water, and the granting of time interval consists of 3 levels of fertilizer that is 10 days, 20 days , and 30 days. Theobserved parameters include high plant at the age of 20, 30 and 40 HST, the diameter of the base of the stem at the age of 20, 30 and 40 HST, number of leaves at the age of 20, 30, and 40 HST, the number and weight of fruit is the fruit of Eggplant are calculated at the time of harvest. The results showed that concentrations of POC sea horse star very real effect against all the parameters of growth and production plants of Eggplant is observed. Growth and production of the best Eggplant plants found at a concentration of treatment 3 cc/liter of water. Time interval of granting POC sea horse Star very real effect against all the independent growth and production plants of Eggplant is observed. Best Eggplant cropproduction, namely the granting of time interval of fertilizer treatment 10 days and 20 days. Keyword : Eggplant, POC Sea Horse Star, Time Interval